Best Available Techniques Principle: International Treaties and Drafting in National Legislation - Tomažič Luka Martin (LeXonomica, 2022)
Best available techniques (BAT) is a legal principle with origins in public international law. Through the activities of drafters at national levels, it finds its various expressions in the legal systems of individual states. This article will analyse the possible approaches to including the BAT principle in national legislation and the general guidelines that drafters should follow to achieve the desired effectiveness of legislation. International treaties are to be understood as partial drafting instructions. A case study will be made for the Slovenian legal system, where the expression of the BAT principle within the Slovenian national regulatory framework will be critically evaluated. Povzetek. Najboljše razpoložljive tehnologije (BAT) so pravno načelo, ki izvira iz mednarodnega javnega prava. Z dejavnostmi pripravljavcev zakonodaje na nacionalnih ravneh je dobilo različne izraze v pravnih sistemih posameznih držav. V tem članku bodo analizirani možni pristopi k vključitvi načela BAT v nacionalno zakonodajo in splošne smernice, ki bi jih morali upoštevati pripravljavci zakonodaje, da bi dosegli želeno učinkovitost zakonodaje. Mednarodne pogodbe je treba razumeti kot delna navodila za pripravo besedil. Izdelana bo študija primera slovenskega pravnega sistema, kjer bo kritično ovrednoteno izražanje načela BAT v slovenskem nacionalnem zakonodajnem okviru.